Which firms train disadvantaged youth? - Mohrenweiser, Jens [Verfasser] (My University, 2012)
"The integration of disadvantaged youth into the labour market is a challenging policy issue. Since young people gain most from work experience and learning provided by firms, hence within apprenticeships, firms play a crucial role in training disadvantaged youths. Knowing firm characteristics that moderate the selection of firms in such training schemes might help to design more effective and efficient policy measures. This paper estimates the determinants of firms that participate in a training programme for disadvantaged youth in Germany. The paper shows that firms with greater training capacity in terms of full-time instructors and own training facilities and firms willing to invest own additional resources in the training of disadvantaged youth are more likely to participate in this training scheme. On the contrary, firm size, an increasing demand for skilled workers and difficulties in finding apprentices do not influence the participation." (Autorenreferat, BIBB-Doku)

In dem Beitrag wird auf das vom Arbeitgeberverband Südwestmetall initiierte Förderprogramm "M+E-Einstieg" Bezug genommen. Im Rahmen dieses Projektes (Laufzeit 01.07.2010-31.12.2013) werden in 13 SWM-Bezirken benachteiligte Jugendliche von der Schule "abgeholt" und beim Übergang in den Betrieb begleitet. Weitere Unterstützung erhalten die Jugendlichen zudem während ihrer Ausbildung im Betrieb.
Keywords: P 1.7 Benachteiligte; P 1.1 Jugendliche; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.2.4.1.4 Verarbeitendes Gewerbe; I 2.1.2.4 Baden-Württemberg; Benachteiligter Jugendlicher; Benachteiligtenförderung; Berufseinmündung; Erste Schwelle; Ausbildungsbereitschaft; Metallindustrie; Elektroindustrie; Pilotprojekt; Baden-Württemberg